New species of Acraspisoides Hill & Winterton and Bonjeania Irwin & Lyneborg (Diptera: Therevidae: Agapophytinae), with the description of a new genus - Winterton, Shaun L. (Zootaxa, 2007)
The stiletto fly subfamily Agapophytinae is diverse and species rich in Australasia, with numerous undescribed species. A new species of Acraspisoides Hill & Winterton, A. monticola sp. nov., is described from females collected in montane localities in eastern Australia. Eight new species of Bonjeania Irwin & Lyneborg are also described, raising the total number of known species to 18. Five new species, B. affinis sp. nov., B. apluda sp. nov., B. bapsis sp. nov., B. webbi sp. nov. and B. zwicki sp. nov., all have a distinctive, forward-protruding head with antennae on a raised tubercle. Two other new species, B. argentea sp. nov. and B. jefferiesi sp. nov., are closely related to B. segnis (White), with very similar shaped male genitalia and body shape. An eighth species, B. lambkinae sp. nov., is closely related to B. clamosis Winterton & Skevington. Bonjeania and Acraspisoides are diagnosed and revised keys to species presented. An unusual new therevid, Vomerina humbug gen. et sp. nov., is also described and figured based on a series of males from New South Wales. This new genus likely represents the sister taxon to Bonjeania.